Hydroxyl polymer coating opening covering strip adhesive tape

By using coated cover strip tape made of polar hydroxypolymer coating, the problems of the decreasing adhesion force of traditional coatings on waterproof coils are solved, and effective bonding in thicker areas is achieved. Excellent bonding power.

CN119410284APending Publication Date: 2025-02-11KEJIAN POLYMER MATERIALS (SHANGHAI) CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411536165.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The existing pre-paved waterproof coils are susceptible to physical damage during cross-operation, and traditional coatings cannot be transparent due to the large filler particle size, resulting in reduced adhesion and hidden dangers of water seepage.

Method used

Use coated cover strip tape made of polar hydroxy polymer coating. The coating consists of polar hydroxy polymer, water, pH adjuster, wetting agent and crosslinking agent. After crosslinking, it can withstand cold water and be able to Alkaline soluble ensures that the concrete hydration layer can penetrate and form effective bonding.

Benefits of technology

Effective bonding in thicker areas is achieved, excellent bonding is maintained, water seepage problem is avoided, and surface adhesive caused by the migration of the plasticizer of the self-adhesive layer is avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119410284A_ABST
    Figure CN119410284A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of high polymer materials, and provides a hydroxyl polymer coating opening covering strip adhesive tape which comprises a hydroxyl polymer coating, a first self-adhesive layer, a blank body layer and a second self-adhesive layer which are sequentially attached together. The hydroxyl polymer coating is obtained by coating and drying a hydroxyl polymer coating; the hydroxyl polymer coating comprises the following components in parts by mass: 10-30 parts of a polar hydroxyl polymer; 1-5 parts of a pH regulator; 0.5 to 1 part of a wetting agent; 2-4 parts of a first cross-linking agent; and 0.5-1 part of a second cross-linking agent. The adhesive tape uses the polar polyhydroxy polymer coating as the coating, the strong polarity can prevent non-polar plasticizers such as mineral oil and polyisobutene of the self-adhesion layer from moving to the polymer coating, and surface adhesion is not prone to occurring; and although the polyhydroxy polymer coating has good hydrophilicity, the polyhydroxy polymer coating can resist cold water after crosslinking, and due to the fact that the polyhydroxy polymer coating can be alkali-soluble, even if the coating is thick, hydrates of post-poured concrete can penetrate through the coating to be in contact with the self-adhesive layer, so that excellent adhesive strength is maintained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a hydroxy polymer coating cover strip adhesive tape. Background Art

[0002] Pre-laid waterproofing membranes are all laid on the base without any gaps. In cross-operation, various types of work can easily cause physical damage to the surface of the waterproofing membranes. Traditional pre-laid waterproofing membranes are often difficult to cut and repair due to their width and weight limitations. It is necessary to develop coating cover tapes for local repair of pre-laid waterproofing membranes, penetrating mechanical fixed covering seals, corner point seals, and overlapping edge reinforcement seals, so as to effectively repair damaged points and strengthen local weak bonding areas, and ensure the continuity and reliability of waterproofing materials.

[0003] CN220297995U discloses a repair tape with an organic-inorganic composite coating protective layer as a temporary protective layer, wherein the organic-inorganic composite coating protective layer is sequentially stacked with a polymer coating layer and a particle layer from top to bottom, the polymer coating layer is at least one of acrylic polymer, polyvinyl acetate, polyethylene vinyl acetate copolymer, acrylate-styrene, acrylate-vinyl acetate, chloroprene rubber, butyl rubber, styrene-butadiene and SEBS, the material of the particle layer is at least one of partially hydrated cement, fully hydrated cement, calcium carbonate, silicate sand, river sand, amorphous silicon dioxide, slag, trihydrated aluminum oxide, slate ash, granite ash, calcite, quartz, zeolite, vermiculite, bauxite, shale, feldspar, perlite, silicate and aluminate, and the particle size of the particle layer is 100-1000 μm. This coating cannot be transparent due to the large filler particle size.

[0004] CN220298024U discloses a repair tape with a polymer coating layer as a temporary protective layer, wherein the polymer coating layer is at least one of acrylic polymer, polyvinyl acetate, polyethylene vinyl acetate copolymer, acrylate-styrene, acrylate-vinyl acetate, chloroprene rubber, butyl rubber, styrene-butadiene and SEBS. The polymer coating of the present invention generally has good water resistance and is also non-alkali soluble.

[0005] In areas with thicker thickness, the above-mentioned coating has a rapid decrease in bonding strength and a risk of water seepage because the silicate hydration layer in the post-poured concrete cannot penetrate the coating and the self-adhesive layer to form an effective bond.

[0006] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention and should not be regarded as an acknowledgment or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art. Summary of the invention

[0007] The present invention is made to solve the above problems and aims to provide a hydroxy polymer coated cover strip tape.

[0008] The invention provides a hydroxyl polymer coating cover strip adhesive tape, which has the following characteristics and comprises: a hydroxyl polymer coating, a first self-adhesive layer, a body layer and a second self-adhesive layer which are sequentially bonded together; wherein the hydroxyl polymer coating is obtained by coating and drying a hydroxyl polymer coating, and the hydroxyl polymer coating comprises the following components in terms of mass fraction: polar hydroxyl polymer: 10-30 parts; pH adjuster: 1-5 parts; wetting agent: 0.5-1 parts; first cross-linking agent: 2-4 parts; second cross-linking agent: 0.5-1 parts.

[0009] The hydroxy polymer coated cover strip tape provided by the present invention may also have the following characteristics: wherein the polar hydroxy polymer is a polyhydroxy water-soluble polymer, the wetting agent is sodium salt of di-2-ethylhexyl succinate, the first cross-linking agent is ammonium zirconium carbonate, the second cross-linking agent is zinc oxide, and the pH regulator is ammonia water.

[0010] The hydroxy polymer coated cover strip adhesive tape provided by the present invention may also have the following characteristics: wherein the polyhydroxy water-soluble polymer is polyvinyl alcohol containing carboxylic acid or starch containing carboxylic acid, the sodium salt of di-2-ethylhexyl succinate is HYDROPALAT WE 3475 produced by BASF, the effective concentration of ammonium zirconium carbonate is 10% to 100%, the zinc oxide is indirect zinc oxide, which complies with GB / T3185 Grade I or II and has a purity of ≥99.4%, and the ammonia water is industrial grade ammonia water with a concentration of 25% to 28%.

[0011] The hydroxy polymer coated cover strip adhesive tape provided by the present invention may also have the following characteristics: wherein the hydroxy polymer coating further comprises 60-90 parts of water by mass.

[0012] The hydroxy polymer coated cover strip adhesive tape provided by the present invention may also have the following feature: wherein the water is tap water or deionized water.

[0013] The hydroxy polymer coated cover strip adhesive tape provided by the present invention may also have the following characteristics: wherein the first self-adhesive layer and the second self-adhesive layer are made of the same material, namely, SBC hot-melt pressure-sensitive adhesive.

[0014] The hydroxy polymer coated cover strip adhesive tape provided by the present invention may also have the following feature: wherein the embryo layer is a PET film.

[0015] The hydroxyl polymer coated cover strip adhesive tape provided by the present invention may also have the following characteristics: wherein the hydroxyl polymer coated cover strip adhesive tape further comprises a release layer bonded to the second self-adhesive layer.

[0016] The hydroxyl polymer coated cover strip tape provided by the present invention may also have the following characteristics: wherein the thickness of the hydroxyl polymer coating is 0.03mm-0.2mm, the thickness of the first self-adhesive layer is 0.1mm-0.5mm, the thickness of the embryo layer is 0.05mm-0.2mm, the thickness of the second self-adhesive layer is 0.1mm-0.5mm, and the thickness of the release layer is 0.02mm-0.1mm.

[0017] The hydroxy polymer coated cover strip adhesive tape provided by the present invention may also have the following characteristics: wherein the release layer is a release film or a release paper, and the release paper is a double-sided release paper.

[0018] Functions and Effects of the Invention

[0019] The hydroxy polymer coating cover strip adhesive tape prepared by the present invention uses a polar polyhydroxy polymer coating as a coating. The strong polarity can prevent non-polar plasticizers such as mineral oil and polyisobutylene in the self-adhesive layer from migrating to the polymer coating, and surface adhesion is not easy to occur. In addition, although the polyhydroxy polymer coating has good hydrophilicity, it can withstand cold water after cross-linking. Since it is alkali-soluble, the hydrate of the post-cast concrete can pass through the coating and contact the self-adhesive layer even when the coating is thick, thereby maintaining excellent adhesion. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 It is a schematic structural diagram of the hydroxy polymer coating cover strip adhesive tape of the present invention;

[0021] Figure 2 The present invention is a schematic diagram of the process of the hydroxy polymer coating cover strip adhesive tape. DETAILED DESCRIPTION

[0022] In order to make the technical means, creative features, objectives and effects of the present invention easy to understand, a hydroxy polymer coated cover strip tape of the present invention is specifically described below in conjunction with embodiments and drawings.

[0023] Unless otherwise specified, the raw materials used in the present invention are purchased through general commercial channels. All test standards not mentioned are national standards.

[0024] Figure 1 It is a schematic structural diagram of the hydroxy polymer coated cover strip tape of the present invention.

[0025] like Figure 1 As shown, the hydroxyl polymer coated cover strip tape is a 5-layer structure sequentially bonded together, which includes, from top to bottom, a hydroxyl polymer coating L1, a first self-adhesive layer L2, a body layer L3, a second self-adhesive layer L4 and a release layer L5.

[0026] The thickness of the hydroxy polymer coating is 0.03 mm to 0.2 mm, preferably 0.03 mm to 0.1 mm.

[0027] The thickness of the first self-adhesive layer is 0.1 mm to 0.5 mm, and the material can be SBC hot melt pressure sensitive adhesive or butyl adhesive, preferably SBC hot melt pressure sensitive adhesive, and the thickness is preferably 0.1 mm to 0.2 mm. When butyl adhesive is selected, the thickness is preferably 0.2 mm to 0.4 mm.

[0028] The thickness of the embryo body layer is 0.05 mm to 0.2 mm, and preferably a PET film with a thickness of 0.05 mm to 0.1 mm is used as the embryo body.

[0029] The thickness of the second self-adhesive layer is 0.1mm-0.5mm, preferably 0.2mm-0.4mm. The material is SBC hot melt pressure sensitive adhesive or butyl adhesive, preferably SBC hot melt pressure sensitive adhesive, and the thickness is preferably 0.1mm-0.2mm. When butyl adhesive is selected, the thickness is preferably 0.2mm-0.4mm.

[0030] The material and thickness of the second self-adhesive layer can be the same as those of the first self-adhesive layer, or can be controlled independently, but preferably the material and thickness are the same as those of the first self-adhesive layer.

[0031] The thickness of the release layer is 0.02 mm to 0.1 mm. The release layer needs to be torn off when used, and is a release film or release paper, preferably a double-sided release paper with a thickness of 0.02 mm to 0.05 mm.

[0032] The hydroxy polymer coating is obtained by coating and drying a water-based hydroxy polymer coating, and is prepared from the following components in proportion by mass:

[0033] Hydroxyl polymer: 10-30 parts;

[0034] Water: 60-90 parts;

[0035] pH regulator: 1-5 parts;

[0036] Wetting agent: 0.5-1 part;

[0037] Cross-linking agent 1: 2-4 parts;

[0038] Cross-linking agent 2: 0.5-1 part;

[0039] The raw materials involved in the above-mentioned hydroxy polymer coating include

[0040] Hydroxyl polymers are polyhydroxy water-soluble polymers that are cold-water resistant but alkali-soluble after film-forming and cross-linking. Polyvinyl alcohol containing carboxylic acid or starch containing carboxylic acid is preferred. Polyvinyl alcohol (PVOH) containing carboxylic acid, with an alcoholysis degree of 85-99% and a polymerization degree greater than 1000 is more preferred, such as Elvanol 80-18 from Kuraray, which contains carboxylic acid PVOH, with an alcoholysis degree of 99% and a polymerization degree of 1700. Another example is POVAL 25-88KL from Kuraray, which contains carboxylic acid PVOH, with an alcoholysis degree of 88% and a polymerization degree of 1750; another example is Dongguan Dongmei Starch DM609, which is an oxidized hydroxypropyl starch containing carboxylic acid.

[0041] The water is tap water or deionized water; the pH regulator is industrial-grade ammonia water with a concentration of 25%-28%.

[0042] Wetting agent is an auxiliary agent that can reduce surface tension, preferably di-2-ethylhexyl succinate sodium salt, such as BASF's HYDROPALAT WE 3475, which is a 75% solution of di-2-ethylhexyl succinate sodium salt.

[0043] The first crosslinking agent is ammonium zirconium carbonate, industrial grade, effective concentration 10-100%, which can react with PVOH or starch, such as Hubei Chengfeng Chemical Ammonium Zirconium Carbonate (20wt%). The second crosslinking agent is zinc oxide, preferably indirect zinc oxide, in accordance with GB / T3185 I or II grade, purity ≥ 99.4%, such as Shanghai Oucheng Zinc Industry Zinc Oxide 121, purity 99.7%.

[0044] The self-adhesive layer is SBC hot melt pressure sensitive adhesive or butyl adhesive. The embryo body is a PET film. The release layer is a release film or release paper, preferably a double-sided release paper.

[0045] Figure 2 The present invention is a schematic diagram of the process of the hydroxy polymer coating cover strip adhesive tape.

[0046] like Figure 2 As shown, the preparation of the hydroxy polymer coated cover strip tape includes the following steps:

[0047] Step 1. Preparation of water-based polymer coating: Add starch or polyvinyl alcohol and water into a stirring kettle 7, stir and disperse evenly; add a pH regulator, stir for 1-6 hours at room temperature or heated to 80-95°C to obtain a transparent uniform solution; add a wetting agent, a cross-linking agent ammonium zirconium carbonate and zinc oxide and stir for another 30-60 minutes; cool to below 50°C and discharge for use.

[0048] Step 2. Preparation of self-adhesive layer: using a mixer 1, prepare SBC hot melt pressure-sensitive adhesive according to comparative example 3 of a polyurethane-doped SBC hot melt adhesive and its preparation method in invention patent CN117050698A; or prepare butyl adhesive according to example 1 of silane-modified self-adhesive butyl adhesive and waterproof membrane containing silane self-adhesive butyl adhesive in CN113621343B.

[0049] Step 3. Self-adhesive layer coating:

[0050] The SBC hot melt pressure-sensitive adhesive is fed into the hot melt glue cylinder of the double-head coating machine 3, the glue cylinder temperature is 160℃-185℃, the hose temperature is 160-185℃, the coating head temperature is 160-185℃, the glue layer thickness is controlled to be 0.1-0.3mm, and at the same time, it is slit coated on both sides of the PET embryo (third layer) unwound by the first unwinder 3 to obtain the first self-adhesive layer and the second self-adhesive layer. The second self-adhesive layer is then compounded with the release film (fifth layer) unwound by the second unwinder 4 through the pressure roller 5, and is wound by the first winder 6 to obtain the semi-finished product A.

[0051] Step 4. Polymer coating application and striping:

[0052] The water-based polymer coating obtained in step 1 is introduced into the glue tank, and is coated on the first self-adhesive layer of the semi-finished product A unwound by the third unwinder 8 by the glue roller of the anilox roller 9, and the thickness of the dry glue is controlled to be 0.03-0.15 mm. After being baked and dried in the oven 10, it is wound up by the second winder 11 to obtain a large roll of semi-finished product B. The semi-finished product B is finally slit by the slitting machine 12, and then wound up by the third winder 13 to obtain a finished small roll.

[0053] The materials used in the preparation examples, embodiments and comparative examples of the present invention are as follows:

[0054] PVOH POVAL 25-88KL: POVAL 25-88KL from Kuraray, containing carboxylic acid PVOH, alcoholysis degree 88%, polymerization degree 1750;

[0055] Oxidized hydroxypropyl starch DM609: Dongguan Dongmei Starch DM609, an oxidized hydroxypropyl starch containing carboxylic acid;

[0056] PVOH POVAL 5-88MB: Kuraray POVAL 5-88MB, carboxylic acid-free PVOH, alcoholysis degree 88%, polymerization degree 550;

[0057] Potato starch: potato starch without carboxylic acid;

[0058] Water: Deionized water product;

[0059] Ammonia water (26%): industrial grade ammonia water, concentration 26%;

[0060] Wetting agent HYDROPALAT WE 3475: BASF's HYDROPALAT WE 3475, succinic acid di-2-ethylhexyl sodium salt 75% solution;

[0061] Ammonium zirconium carbonate: Hubei Chengfeng Chemical Ammonium zirconium carbonate, effective concentration 20wt%;

[0062] Zinc oxide 121: Shanghai Oucheng Zinc Industry Zinc Oxide 121, purity 99.7%;

[0063] GCC 1158: Shanghai Hangchi heavy calcium carbonate powder, 1200 mesh;

[0064] Dispersant Archor D6601: Shanghai Weiyong Industrial Polyacrylate Dispersant, effective content 41%;

[0065] Thickener PERMUTEX RM-4456: Stahl associative thickener;

[0066] Styrene acrylic emulsion FS-7860: BATF styrene acrylic emulsion, solid content 53%

[0067] Preparation Example 1:

[0068] PVOH Elvanol 80-18: 20 parts;

[0069] Water: 74 parts;

[0070] Ammonia water (26%): 2 parts;

[0071] Wetting agent HYDROPALAT WE 3475: 0.5 parts;

[0072] Ammonium zirconium carbonate: 3 parts;

[0073] Zinc oxide 121: 0.5 parts.

[0074] Process: Add PVOH and water into a stirring kettle, stir and disperse evenly; add pH adjuster, stir at room temperature for 6 hours to obtain a transparent uniform solution; add wetting agent, cross-linking agent ammonium zirconium carbonate and zinc oxide and stir for another 60 minutes; cool to below 50°C and discharge for use.

[0075] Preparation Example 2:

[0076] PVOH POVAL 25-88KL: 20 parts;

[0077] Water: 74 parts;

[0078] Ammonia water (26%): 2 parts;

[0079] Wetting agent HYDROPALAT WE 3475: 0.5 parts;

[0080] Ammonium zirconium carbonate: 3 parts;

[0081] Zinc oxide 121: 0.5 parts.

[0082] The process is the same as that of Preparation Example 1.

[0083] Preparation Example 3:

[0084] Oxidized hydroxypropyl starch DM609: 20 parts;

[0085] Water: 74 parts;

[0086] Ammonia water (26%): 2 parts;

[0087] Wetting agent HYDROPALAT WE 3475: 0.5 parts;

[0088] Ammonium zirconium carbonate: 3 parts;

[0089] Zinc oxide 121: 0.5 parts.

[0090] Process: The raw material PVOH is replaced by starch, and the rest is the same as Preparation Example 1. Preparation Example 4:

[0091] SBC hot melt pressure sensitive adhesive was prepared according to Comparative Example 3 of CN117050698A. Comparative Preparation Example 1:

[0092] PVOH Elvanol 80-18: 20 parts;

[0093] Water: 77.5 parts;

[0094] Ammonia water (26%): 2 parts;

[0095] Wetting agent HYDROPALAT WE 3475: 0.5 parts.

[0096] The process is the same as Preparation Example 1 except that no cross-linking agent is added.

[0097] PVOH POVAL 5-88MB: 30 copies;

[0098] Water: 64 parts;

[0099] Ammonia water (26%): 2 parts;

[0100] Wetting agent HYDROPALAT WE 3475: 0.5 parts;

[0101] Ammonium zirconium carbonate: 3 parts;

[0102] Zinc oxide 121: 0.5 parts.

[0103] The process is the same as that of Preparation Example 1.

[0104] Comparative Preparation Example 3:

[0105] Potato starch: 20 parts;

[0106] Deionized water: 74 parts;

[0107] Ammonia water (26%): 2 parts;

[0108] HYDROPALAT WE 3475: 0.5 parts;

[0109] Ammonium zirconium carbonate: 3 parts;

[0110] Zinc oxide 121: 0.5 parts.

[0111] Process: Add potato starch and water into a stirring tank, stir and disperse evenly; add pH adjuster, heat to 95℃ and stir for 6 hours to obtain a transparent, uniform and viscous solution; add wetting agent, cross-linking agent ammonium zirconium carbonate and zinc oxide and stir for another 60 minutes; cool to below 50℃ and discharge for use.

[0112] Comparative Preparation Example 4:

[0113] Water: 31.5 parts;

[0114] Ammonia water (26%): 0.5 parts;

[0115] Wetting agent HYDROPALAT WE 3475: 0.5 parts;

[0116] GCC 1158: 37 copies;

[0117] Dispersant Archor D6601: 0.5 parts;

[0118] Thickener PERMUTEX RM-4456: 3 parts;

[0119] Styrene acrylic emulsion FS-7860: 27 parts;

[0120] Process: Add water, ammonia, wetting agent, dispersant, GCC 1158 and thickener into a stirring kettle. Stir at high speed for 60 minutes to check if there are no particles. Add styrene acrylic emulsion FS-7860 and continue stirring at medium speed for 30 minutes to obtain a uniform colloid. Cool to below 50°C and discharge for use.

[0121] Test Example 1:

[0122] This test example tests the basic properties of the waterborne polymer coatings of Preparation Examples 1 to 3 and Comparative Preparation Examples 1 to 4. The results are shown in Table 1. The test method is as follows:

[0123] Appearance: visual inspection;

[0124] Viscosity -23℃: Tested according to GB / T 2794-2013 method;

[0125] Solid content: tested according to GB / T2793-1995 method;

[0126] Roller coating operability: Observe whether the paint has skinning or coating leakage when roller coating.

[0127] Table 1. Basic properties of waterborne polymer coatings in Preparation Examples 1 to 3 and Comparative Preparation Examples 1 to 4

[0128]

[0129]

[0130] Examples 1-3 and Comparative Examples 1-4

[0131] The compositions of the adhesive tapes of Examples 1-3 and Comparative Examples 1-4 are shown in Table 2.

[0132] The preparation methods of the adhesive tapes of Examples 1-3 and Comparative Examples 1-4 are briefly described as follows:

[0133] The SBC hot melt adhesive obtained in Preparation Example 4 was fed into the hot melt adhesive cylinder of the coating machine. The temperature of the adhesive cylinder / adhesive hose / coating head was set to 180°C, and the thickness was controlled to 0.15 mm. It was coated on both sides of the third layer of PET embryo body at one time through a double-head slit coating die to obtain the second and fourth self-adhesive layers. The fourth layer and the fifth layer of double-sided release paper were rolled up to obtain a semi-finished product A (see Figure 2 );

[0134] The water-based polymer coating obtained in Preparation Examples 1-3 and Comparative Preparation Examples 1, 2, and 4 was introduced into the glue tank, coated on the second layer (first self-adhesive layer) by an anilox roller, and the dry glue thickness was controlled to be 0.05 mm (Examples 2 and 3 were controlled to be 0.15 mm and 0.03 mm, respectively). After being baked and dried in an oven, a large roll of semi-finished product B was obtained after winding; the semi-finished product B was finally wound by a slitting machine to obtain a finished small roll.

[0135] Table 2. Composition of Examples and Comparative Examples

[0136]

[0137]

[0138] Test Example 2

[0139] This test example tests the properties of the adhesive tapes prepared in Examples 1-3 and Comparative Examples 1-5. The results are shown in Table 3. The test method is as follows:

[0140] Cold water resistance: After the tape is soaked in 23℃ water for 7 days, the coating is rinsed with tap water for 1 minute and dried at room temperature for 3 days. Touch the surface with your hand to see if it is sticky;

[0141] Re-adhesion: Store at 70℃ for 7 days and then cool to room temperature for 24 hours. Touch with your hand to see if it is sticky.

[0142] Peeling strength with post-cast concrete: tested according to Section 6.20 of GB / T23457-2017.

[0143] The test results of the comparative examples and embodiments are shown in Table 3.

[0144] Table 3. Performance comparison of examples and comparative examples

[0145]

[0146] As can be seen from Table 3, Examples 1-3 are all cold water resistant (non-sticky), while Comparative Examples 1 and 2 are not cold water resistant (sticky) because no crosslinking agent is used or the PVOH does not contain carboxylic acid and has a small molecular weight. Even if the coating thickness of Example 3 is only 0.03mm, it does not have re-stickiness after storage at 70℃x7d, and has excellent plasticizer migration barrier ability. Comparative Example 3 cannot be coated because of its high consistency and gel-like state. Comparative Example 4 is a coating with a common styrene-acrylic emulsion as a film-forming material. Due to the migration of the plasticizer in the second self-adhesive layer, it is sticky, and workers are prone to sticking to the soles of their shoes during construction, which is not conducive to construction.

[0147] In Example 2, effective bonding can still be formed after the thickness reaches 0.15 mm, indicating that the hydration layer of the concrete can dissolve and penetrate the coating and the self-adhesive layer to form effective bonding due to its strong alkalinity, and the peeling force is greater than 1.5 N / mm; while in Comparative Example 5, the coating with styrene acrylic emulsion as the film-forming material has a peeling force reduced to 0.3 N / mm after the thickness reaches 0.15 mm, indicating that the hydration layer of the concrete cannot penetrate the coating and the self-adhesive layer to form effective bonding.

[0148] The above-mentioned embodiments are preferred examples of the present invention and are not intended to limit the protection scope of the present invention.

Claims

1. A hydroxy polymer coated cover tape, characterized in that: include: A hydroxy polymer coating, a first self-adhesive layer, a body layer and a second self-adhesive layer are sequentially laminated together; The hydroxyl polymer coating is obtained by coating and drying a hydroxyl polymer coating, and the hydroxyl polymer coating comprises the following components in proportion by mass: Polar hydroxy polymer: 10-30 parts; pH regulator: 1-5 parts; Wetting agent: 0.5-1 part; First cross-linking agent: 2-4 parts; Second cross-linking agent: 0.5-1 part.

2. The hydroxy polymer coated cover tape according to claim 1, characterized in that: in, The polar hydroxy polymer is a polyhydroxy water-soluble polymer. The wetting agent is di-2-ethylhexyl succinate sodium salt, The first cross-linking agent is ammonium zirconium carbonate, The second cross-linking agent is zinc oxide, The pH regulator is aqueous ammonia.

3. The hydroxy polymer coated cover tape according to claim 2, characterized in that: in, The polyhydroxy water-soluble polymer is polyvinyl alcohol containing carboxylic acid or starch containing carboxylic acid, The sodium salt of di-2-ethylhexyl succinate is HYDROPALAT WE 3475 produced by BASF. The effective concentration of the ammonium zirconium carbonate is 10% to 100%. The zinc oxide is indirect zinc oxide, which meets GB / T3185 Grade I or II, and has a purity of ≥99.4%. The ammonia water is industrial-grade ammonia water with a concentration of 25%-28%.

4. The hydroxy polymer coated cover tape according to claim 1, characterized in that: in, The hydroxy polymer coating further comprises 60-90 parts of water by mass.

5. The hydroxy polymer coated cover tape according to claim 4, characterized in that: in, The water is tap water or deionized water.

6. The hydroxy polymer coated cover tape according to claim 1, characterized in that: in, The first self-adhesive layer and the second self-adhesive layer are made of the same material, which is SBC hot-melt pressure-sensitive adhesive.

7. The hydroxy polymer coated cover tape according to claim 1, characterized in that: in, The embryo body layer is a PET film.

8. The hydroxy polymer coated cover tape according to claim 1, characterized in that: in, The hydroxyl polymer coated cover strip tape further comprises a release layer bonded to the second self-adhesive layer.

9. The hydroxy polymer coated cover tape according to claim 8, characterized in that: in, The thickness of the hydroxy polymer coating is 0.03 mm to 0.2 mm. The thickness of the first self-adhesive layer is 0.1 mm-0.5 mm. The thickness of the embryo layer is 0.05mm-0.2mm. The thickness of the second self-adhesive layer is 0.1 mm to 0.5 mm. The thickness of the release layer is 0.02 mm-0.1 mm.

10. The hydroxy polymer coated cover tape according to claim 8, characterized in that: in, The release layer is a release film or a release paper, and the release paper is a double-sided release paper.

Citation Information

Patent Citations

  • Silane-modified self-adhesive butyl adhesive and waterproof membranes containing silane self-adhesive butyl adhesive

    CN113621343B

  • Polyurethane doped SBC hot melt adhesive and preparation method thereof

    CN117050698A